2016
DOI: 10.1111/sms.12692
|View full text |Cite
|
Sign up to set email alerts
|

Effects of the foot strike pattern on muscle activity and neuromuscular fatigue in downhill trail running

Abstract: Minimizing musculo-skeletal damage and fatigue is considered paramount for performance in trail running. Our purposes were to investigate the effects of the foot strike pattern and its variability on (a) muscle activity during a downhill trail run and (b) immediate and delayed neuromuscular fatigue. Twenty-three runners performed a 6.5-km run (1264 m of negative elevation change). Electromyographic activity of lower-limb muscles was recorded continuously. Heel and metatarsal accelerations were recorded to iden… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(28 citation statements)
references
References 40 publications
0
27
0
1
Order By: Relevance
“…3 a Schematic representation of the time course of alterations following downhill running (DR) and b current scientific evidence on the benefits of different adaptation strategies to DR (i.e. prior exposure to DR [46,63,67,68,85,92,121,141,143,165,181,184,185,192,193,196,197], preconditioning strategies [16,81], DR training [14,209,210,254], changes in stride pattern [32,67,68,218,219,221,220,228,255], the use of lower limb compression garments [15,236,237], and the use of specific footwear [28,149,253,256]. In a and b, orange, blue, red, purple, and green spheres correspond to isometric MVC force/torque loss, changes in running economy and mechanics, ultrastructural alterations, inflammation and oedema, and muscle soreness, respectively.…”
Section: Prior Exposure To Downhill Runningmentioning
confidence: 99%
See 1 more Smart Citation
“…3 a Schematic representation of the time course of alterations following downhill running (DR) and b current scientific evidence on the benefits of different adaptation strategies to DR (i.e. prior exposure to DR [46,63,67,68,85,92,121,141,143,165,181,184,185,192,193,196,197], preconditioning strategies [16,81], DR training [14,209,210,254], changes in stride pattern [32,67,68,218,219,221,220,228,255], the use of lower limb compression garments [15,236,237], and the use of specific footwear [28,149,253,256]. In a and b, orange, blue, red, purple, and green spheres correspond to isometric MVC force/torque loss, changes in running economy and mechanics, ultrastructural alterations, inflammation and oedema, and muscle soreness, respectively.…”
Section: Prior Exposure To Downhill Runningmentioning
confidence: 99%
“…rear-, mid-and fore-foot) can influence the mechanical strain applied to lower limb muscles during running [214][215][216][217]. Accordingly, manipulating foot stride frequency [218] and foot strike pattern [219] during DR could reduce EIMD including neuromuscular fatigue. Following an intermittent 45-min treadmill DR (9 × 5-min; slope: − 15%; speed: 10.5 km h −1 ), Rowlands et al [68] reported lower MVC torque decrements post-DR using an understride strategy (− 8.8% MVC torque; 92% preferred stride length) compared with an overstride (− 14.7% MVC torque; 108% preferred stride length) or preferred stride strategy (− 15.5% MVC torque).…”
Section: Optimisation Of Stride and Foot Strike Patternmentioning
confidence: 99%
“…Consequently, the negative work done by both KE and PF muscles is about twofold greater during DHR with a -8.3% slope than during level running as the same speed (4.5 m.s -1 ) ( Buczek and Cavanagh, 1990 ). Therefore, KE or PF fatigue is greater after DHR than level running as a consequence of important absorption function and increased electromyographic activities ( Giandolini et al, 2016a , 2017 ; Maeo et al, 2017 ). As a matter of fact, the increase in vertical downward velocity associated with higher ground reaction forces experienced during DHR might accentuate soft-tissue vibrations ( Dewolf et al, 2016 ) and in turn, muscle activity.…”
Section: Introductionmentioning
confidence: 99%
“…This suggestion is also reinforced by the fact that both the 35 km and 55 km MTR had similar average negative slopes (8.9 and 8.0, respectively), so the greatest difference between races was the total negative distance covered in the 55 km MTR. Therefore, it can be concluded that although other intrinsic factors that were not measured during the races, such as pace fluctuations [13] or foot strike pattern variability [18], may substantially influence the degree of muscle damage, in the present study the downhill running distance was a relevant factor inducing slow (type I) fibre sarcomere damage.…”
Section: Km Mtrmentioning
confidence: 66%
“…There is general agreement that MTRs lead to muscle damage because of the strenuous competitive conditions [36]. The mechanical stress associated with eccentric contractions during downhill running causes damage to the fibre cytoskeleton, and produces inflammation and delayed-onset muscle soreness [16,18]. During flat running, in which the eccentric impact is lower, it has been established that the total running distance covered or the time spent running is related to the extent of muscle damage [39,47].…”
Section: Introductionmentioning
confidence: 99%